0081 Change in respiratory heat flows in response to wearing half-mask respirators in hot-and-humid environment. (21st August 2017) - Chen, Chen-Peng; Lin, Yi-Chun; Wei, Hui-Chen
Abstract : Objectives: When using a respirator a microenvironment develops around the nasal cavity. The heat load in this microenvironment deviates from that in the ambient air, shifting the paradigm of metabolic heat transfer via respiratory heat flows. This study determined the change in respiratory heat flows among users of half-mask respirators under different thermal conditions. Methods: Twenty-five participants (13 males and 12 females) were required to wear two models of half-mask respirators (one filtering facepiece without exhalation valve and one elastomeric facepiece with valve) and walked on stairs (130–200 W/m 2 ) for 30 min in a climatic chamber. Combinations of air temperature (25, 29, and 33°C) and relative humidity (55% and 75%) were applied to develop various levels of heat stress. Results: The temperature of the respired air taken inside the filtering facepiece was greater than the level inside the elastomeric facepiece. Using the ISO/TS 16976–5 model, a reduction in the respiratory convective and evaporative heat flows was observed when the heat load in the ambient air was raised (R 2 =0.447 and 0.470, respectively). The difference between the respiratory heat flow via convection and that via evaporation decreased as the heat stress from the ambient air increased when the filtering facepiece was used (0.721). Conclusions: The metabolic heat built up in the microenvironment inside a respirator without an exhalation valve could alter the development of respiratory heat flows. Caution should be exercised to prevent imbalance in thermoregulation when using these respirators in hot-and-humid conditions.